(untitled) (International Journal of Applied Research in Management and Economics, 2018)
Contrary to the neoclassical view, the population and its components are one of the factors affecting long-term economic growth. Some studies have pointed to the negative impact of population growth and others on its positive impact. The purpose of this paper is to examine the impact of population growth on economic growth from 1985 to 2007 and 1985 to 2016 among the 32 member countries of the upper-middle-income group. Using World Bank data (2016) and the panel’s method, the impact of population growth and birth rate on economic growth in two continuous periods has been investigated. The results show that the more we approach the present time, the impact of population growth and birth rate on economic growth in upper-middle-income countries decreases; consequently if the effect of these two components i.e population growth and birth rate is not controlled in this group of countries and countries with lower income, it will be led a negative effect on economic growth. Therefore, considering this research, the effect of demographic factors can be shown in the long-term; it is important to note that by declining population growth and birth rate in this group of countries, investment, the productivity of the workforce and the population in the age of activity increases. Economic growth reduces due to the disruption of the balance and the increase in population on economic power. By increasing one unit of the population growth, economic growth has achieved to 0.17% reduction in 2016 from a 0.26% increase in 2007.